Do long delay conditioned stimuli develop inhibitory properties? - Escobar, Martha; Suits, W. T.; Rahn, Elizabeth J.; Arcediano, Francisco (Frontiers in Psychology, 2015)
In long-delay conditioning, a long conditioned stimulus (CS) is paired in its final segments with an unconditioned stimulus. With sufficient training, this procedure usually results in conditioned responding being delayed until the final segment of the CS, a pattern of responding known as inhibition of delay. However, there have been no systematic investigations of the associative structure of long delay conditioning, and whether the initial segment of a long delay CS actually becomes inhibitory is debatable. In an appetitive preparation with rat subjects, the initial segment of long delay CS A passed a retardation (Experiment 1a) but not a summation (Experiment 1b) test for conditioned inhibition. Furthermore, retardation was observed only if long delay conditioning and retardation training occurred in the same context (Experiment 2). Thus, the initial segment of a long delay CS appears to share more characteristics with a latent inhibitor than a conditioned inhibitor. Componential theories of conditioning appear best suited to account for these results.